Some Structural Features of the Antarctic Ocean and Antarctica on the Basis of Gravimetric Data (Nekotorye Cherty Struktury Yuzhnogo Okeana i Antarktiki po Gravimetricheskim Dannym) - Vashchilov,Yu. Ya.; Stroev,P. A. (1974)
The gravity field of Antarctica has been studied very little, but the gravity field of the Antarctic Ocean has been studied even less. Japanese specialists performed gravimetric investigations in the sector between Australia, New Zealand and Antarctica. The main part of the gravity measurements fall in the Indian sector of the Anarctic Ocean; only single profiles and points, and some observations on some islands are available in the Pacific and Atlantic sectors. Latitudes in the forties and fifties are the most poorly studied because of continuous storms. The coastal waters of Antarctica are studied much better. Gravimetric points to encircle Antarctica with an almost closed ring in a band from 60 degrees to the coast of the continent and make it possible to describe the nature of the gravity field in these regions. Trans. of Antarktika (USSR) n11 p73-83 1972, by Walter L. Burton.